Application of gis - technology for modelling motion water in the open channels - Venherskyi, Petro; Kokovska, Yaryna (Видавництво Львівської політехніки, 2012)
In this paper technology that would be allowed to use ArcGIS-Extension, that is GIS-components for Webapplications based on ArcGIS Server'a. Such technologies provide simple and easy integration and use of GIS-component on the WEB-site, where a separate layer provided opportunities modeling and solving applied problems of moving water flow in rivers.
Keywords: equation of motion of fluid; speed of flow; section of river-bed; pressure motion; projection equation